The Effect of Perceived Benefit and Perceived Risk on Purchase Decisions That are Mediated By Purchase Intention Using The Alfagift Application - Erick Alviyendra; Ratlan Pardede (PT. Publikasiku Academic Solution, 2024)
This study aims to analyze the influence of perceived benefit and perceived risk on purchase decisions mediated by purchase intention in Alfagift application users. Perceived benefit refers to the benefits felt by consumers when using an application, while perceived risk relates to potential losses or uncertainties that may be faced. Purchase intention is the consumer's intention to buy, which is influenced by the perception of benefits and risks. This study uses a quantitative approach with a survey method to collect data from Alfagift application users. Data analysis was carried out using multiple regression models and path analysis to test the role of purchase intention as a mediating variable. The results of the study show that perceived benefits have a significant positive influence on purchase intention and purchase decision. On the other hand, perceived risk has a negative effect on purchase intention, but does not directly affect purchase decision without being mediated by purchase intention. Purchase intention has proven to be an important mediator in the relationship between perceived benefit, perceived risk, and purchase decision. These findings provide insights for app developers to improve perceived benefits and mitigate risks to drive consumer intent and purchase decisions.